One man's blessing, another woman's curse? Family factors and the gender-earnings gap of doctors - Stefanie Schurer; Daniel Kuehnle; Anthony Scott; Terence Chai Cheng (Institute for the Study of Labor (IZA), 2012)
Using data from a new longitudinal survey of doctors from Australia, the authors test whether observed large gender-pay gaps among general practitioners (GPs) are the result of women's larger willingness to interrupt their careers. On average, female GPs earn A83,000 or 54% less than male GPs. The difference between men and women with children is A105,000, and A45,000 for men and women without children. Of this gap, 66-75% is explained by differences in observable characteristics such as hours worked. The family gap emerges also within the sexes. Female GPs with children experience an earnings penalty of A15,000-A25,000 in comparison to women without children; almost 100% of this difference is due to observable characteristics such as hours worked and career interruptions. Male GPs with children experience a family premium of A35,000 in comparison to men without children, indicating the presence of a breadwinner effect that exacerbates the gender-earnings gap.
Keywords: J24; 330; gender-earnings gap; family-earnings gap; labour force attachment; decomposition methods; family physicians; MABEL